Sugarcane: Boom crop for carbon sequestration - Bhatt, Rajan; Verma, Krishan K; Majumder, Debjyoti (Indian Farming, 2023)
Soils, especially specifically managed agricultural soils can be a large low-cost source of greenhouse gases (GHGs) with extra potential advantages to agricultural output. Most horticultural soil experts and agronomists feel that, most agricultural soils can store lot of carbon and even a slight increase in carbon stocks across large home-stead land regions may result in important GHGs reductions. Sugarcane is one of the crop that can cope with rising carbon dioxide (CO2) levels due to its natural advantages. Some of the major natural endowments in relation to growing CO2 concentrations in the atmosphere include a very low carbon dioxide compensation point and the unique property of sequestering carbon in the form of phytoliths or plant stone. The crop has been given two significant abilities namely, low compensation point (varying between 0–10 ppm) and carbon sequestering capacity (181 kg C sequestered/ha year), which assists in regulating the effect of rising CO2 concentration on the crop.